Prevalence of antibodies against hepatitis C virus in volunteer blood donors (Colombia Medica, 1992)
Using the ELISA technique, 1984 donors to the Blood Bank of the Colombian Red Cross in Cali, Colombia, from March to September 1991, were studied to find the prevalence of hepatitis C antibodies. Results were positive in 0.45% of the donors, a relative low prevalence similar to European countries.